Effect of Filler Variations on Chemical and Microbiological Properties of Tomato Sauce - Dewi, Arum Safriana; Faradiani, Alifa Rahma; Kurniati, Dwitya; Iskandar, Nabila Faradina (Jurnal Ilmu Pangan dan Hasil Pertanian, 2025)
Tomatoes are fruits that contain a variety of phytochemicals and nutrients. To extend shelf life and increase market value, tomatoes can be processed into tomato sauce through grinding and mixing with additional ingredients. One of the added ingredients is a filler, which aims to improve the viscosity and stability of the tomato sauce. This study evaluated the effect of different fillers (papaya and sweet potato) on the chemical characteristics (moisture content, ash content, protein content, fat content, carbohydrate content, energy value, total titratable acidity, and vitamin C) and Total Plate Count (TPC) of tomato sauce. The study employed a Completely Randomized Design (CRD) consisting of F0 (control), F1 (papaya), and F2 (sweet potato). The results showed that the use of papaya as a filler produced tomato sauce with the highest moisture content, while the sweet potato filler increased the energy value. The fillers did not result in significant differences in total titratable acidity and vitamin C content of the tomato sauce. The TPC values of tomato sauce containing papaya and sweet potato fillers exceeded the Indonesian National Standard (SNI) limits but were still within acceptable (satisfactory) levels.